1983
DOI: 10.1128/iai.40.1.429-431.1983
|View full text |Cite
|
Sign up to set email alerts
|

Culture Supernatants of Campylobacter jejuni Induce a Secretory Response in Jejunal Segments of Adult Rats

Abstract: Culture supernatants offour Campylobacterjejuni strains induced a net sodium secretory flux (plasma-lumen) and an impaired glucose transport in perfused jejunal segments of adult rats in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The results of the present study, indicating that C. jejuni infection induces net Na + and CIsecretion and decreases sugar absorption, are in consonance with the in vivo studies by Fernandez et ah [4] in rat small intestine.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study, indicating that C. jejuni infection induces net Na + and CIsecretion and decreases sugar absorption, are in consonance with the in vivo studies by Fernandez et ah [4] in rat small intestine.…”
Section: Discussionsupporting
confidence: 93%
“…A significantly lower o-glucose and o-galactose absorption has been observed in young mice when Campylobacter cultures were given orally [3]. A net sodium secretory flux and decreased glucose absorption has also been shown in vivo in rat jejunal segments perfused with culture supernantants of C. jejuni [4]. The pathophysiological mechanism(s) by which C. jejuni enterotoxin induces fluid and electrolyte loss from the intestinal epithelium of experimental animals and humans is least understood.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Ruiz-Palacios and his colleagues in Mexico, using special culture conditions, have recently shown that many C. jejuni clinical isolates from children produce a heat-labile enterotoxin that raises intracellular cyclic AMP levels, causes cytotonic changes in CHO cells, and induces fluid secretion in ligated rat ileal loops; the secretory activity of this toxin is neutralized by antiserum to cholera toxin (CT) (41). Culture supernatants of these toxigenic strains have also been shown to cause intraluminal secretion of fluid and electrolytes when perfused in vivo through rat jejunal segments (16). * Corresponding author.…”
mentioning
confidence: 99%
“…Both methods display high sensitivity and specificity. In vivo assays to detect enterotoxin activity include the rabbit or rat ileal loop test (RILT) (32,84), or the removable intestinal tie adult rabbit diarrhea (RITARD) model (109).…”
Section: Enterotoxinsmentioning
confidence: 99%